CRITICAL LITERACY IN THE TEACHING OF WRITING HORTATORY EXPOSITION TEXT BASED ON GENRE PEDAGOGY APPROACH - Dewi, Mayang Sari Nirmala (2016)
The research reported in this paper centers around the issue of critical literacy and Genre-based Approach. It particularly aims to investigate how the integration of critical literacy to Genre-based Approach is implemented in the teaching of writing Hortatory Exposition text to tenth graders in a state senior high school in Bandung, West Java, Indonesia. Using a qualitative research design, the data from classroom observation, interview, students' reflective journals, and students' writings were analyzed to investigate how critical literacy is implemented in the teaching of writing Hortatory Exposition text. The analysis of the data is based on the frameworks of Critical Social Literacy: Literacy as a social practice (Kress, 2003), the four dimensions model of critical literacy (Lewison, Flint & van Sluys, 2002), and Genre-based Approach. The analysis reveals that the implementation of critical literacy in contextualized Genre-based Approach (GBA) occurred at the first, second, and fourth stages of GBA. At the first and second stages of GBA, Building Knowledge of the Field and Modelling stages, students were invited to activate their prior knowledge and interpret everyday phenomena with critical lenses. Meanwhile, at the fourth stage of GBA, Independent Construction, the students were invited to communicate their new lines of thinking in written texts. In addition, this practice also led the students not only to be able to convey their critical multiple views but also to be able to organize their views and arguments in systematic and standard organization with specific purpose in form of Hortatory Exposition text. This case study contributes to other research on Genre-based Approach and critical literacy in secondary classroom, especially in English as Foreign Language classroom, which attempt to examine how the integration of critical literacy to Genre-based Approach in the teaching of writing could enhance students' writing and critical capacities.;---Penelitian dalam tesis ini mengenai tentang isu literasi kritis dan pendekatan berbasis genre. Penelitian ini secara spesifik bertujuan untuk menginvestigasi bagaimana integrasi literasi kritis terhadap pendekatan berbasis genre diimplementasikan dalam proses pengajaran menulis teks hortatori eksposisi terhadap siswa kelas sepuluh di sebuah SMA Negeri di Bandung, Jawa Barat, Indonesia. Menggunakan desain kualitatif, data dari penelitian kelas, wawancara, students' reflective journals, dan tulisan siswa dianalisa untuk mengetahui bagaimana literasi kritis diimplementasikan dalam megajar menulis teks hortatori eksposisi. Proses analisa data berdasarkan teori-teori Critical Social Literacy: Literacy as a social practice (Kress, 2003), the four dimensions model of critical literacy (Lewison, Flint & van Sluys, 2002), dan Genre-based Approach. Hasil analisa data menunjukkan bahwa pengimplementasian literasi kritis melalui pendekatan berbasis genre muncul di tahap pertama, kedua, dan keempat dari pendekatan ini. Dalam tahap pertama dan kedua, yaitu tahap Building Knowledge of the Field dan Modelling, siswa diajak untuk mengaktifkan ilmu pengetahuan yang sudah mereka sebelumnya dan menafsirkan fenomena sehari-hari menggunakan sudut pandang kritis mereka. Sementara itu, di tahap keempat, yaitu Independent Construction, siswa diajak untuk mengkomunikasikan pola pikir baru mereka dalam bentuk teks tertulis. Selain itu, sistem pengajaran seperti ini juga mempengaruhi siswa agar tidak hanya sekedar mampu menyampaikan sudut pandang kritis mereka, tetapi juga membantu siswa untuk menyusun ide-ide kritis mereka dalam sebuah teks Hortatori Eksposisi. Penelitian studi kasus ini juga memberikan kontribusi untuk penelitian lain yang bergerak dalam bidang pendekatan berbasis genre dan literasi kritis yang bertujuan untuk menganalisa bagaimana integrasi literasi kritis terhadap pendekatan berbasis genre dalam mengajar menulis mampu meningkatkan kemampuan menulis siswa dan juga kapasitas kriitis mereka.